2020
DOI: 10.1038/s41598-020-77696-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vancomycin-resistant enterococcus in Africa in one health approach: a systematic review and meta-analysis

Abstract: Vancomycin-resistant enterococci are a global challenge currently as reported by the World Health Organization. It is also important to recognize that combating antimicrobial resistance needs to recognize the interconnections between people, animals, plants and their shared environment in creating public health, the so-called One Health approach. Although the presence of VRE has been described in many regions of the world, there is a lack of comprehensive data indicating their prevalence of in Africa. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 73 publications
0
14
0
1
Order By: Relevance
“…The unnoticed small outbreak detected in this work, together with the scarce number of published epidemiological studies detecting VREfm in healthcare institutions of Tunisia since 2007 [ 12 , 13 , 14 , 22 ], highlights the fact that VREfm numbers in this country may be higher than estimated. Indeed, a recent systematic review and meta-analysis developed by Alemayehu and Hailemariam [ 23 ] identified a high-pooled prevalence of VREfm enterococci in African countries, with Tunisia, despite everything, being one of the countries that most contributed to such analysis (just surpassed by South Africa and Ethiopia).…”
Section: Resultsmentioning
confidence: 99%
“…The unnoticed small outbreak detected in this work, together with the scarce number of published epidemiological studies detecting VREfm in healthcare institutions of Tunisia since 2007 [ 12 , 13 , 14 , 22 ], highlights the fact that VREfm numbers in this country may be higher than estimated. Indeed, a recent systematic review and meta-analysis developed by Alemayehu and Hailemariam [ 23 ] identified a high-pooled prevalence of VREfm enterococci in African countries, with Tunisia, despite everything, being one of the countries that most contributed to such analysis (just surpassed by South Africa and Ethiopia).…”
Section: Resultsmentioning
confidence: 99%
“…The more common occurrence of van genes in HWWs from Finland compared to Benin or Burkina Faso suggests that vancomycin-resistant Enterococci (VRE) causing severe difficult-to-treat-infections 16 are more frequent in hospitals in Finland, possibly due to differences in the consumption of vancomycin in different countries. Only one of the West African hospitals reported vancomycin among the most used antibiotics (Supplementary Material, Table S1A).…”
Section: Discussionmentioning
confidence: 99%
“…They can feature an impressive resistance profile in terms of both intrinsic and acquired ARGs and often exhibit multidrug resistant phenotypes. For instance, hospital-associated strains of methicillin-resistant S. aureus (MRSA) carrying the mec 17 gene that encodes a beta-lactamase and vancomycin-resistant Enterococci (VRE) carrying the van gene 16 are clinically important pathogens in hospitals and are both associated with increased mortality 1,18 . However, investigating only bacterial isolates may result in limited understanding of ARGs occurring in a particular hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação a E. faecium, há relatados de aumento significativo da prevalência da resistência a Vancomicina na Turquia, África, Etiópia, Nigéria (Kilbas et al, 2018;Alemayehu et al, 2020;Melese, et al, 2020;Wada, et al, 2020). Além disso, essa mesma tendência de aumento da resistência aos antibióticos, tem sido vista em outros estudos que apontam o aumento da prevalência da resistência aos aminoglicosídeos, tanto em E. faecium quanto em E. faecalis, no Irã e até mesmo no Brasil (Peyvasti, et al, 2020;Jannati et al, 2020;Bender, et al, 2009).…”
Section: Introductionunclassified